Usulan Pengendalian Persediaan dengan Mempertimbangkan Kapasitas Gudang di PT. Charoen Pokphand Indonesia - Dillwyn Felix Johono; Tanti Octavia (Jurnal Titra, 2020)
PT. Charoen Pokphand is a company engaged in the animal feed industry. The company wants to make continuous improvements to facilitate the distribution of animal feed. The initial improvement that needs to be done is to control the amount of inventory of a product by looking at the demand from consumers. The determination of safety stock uses the ABC classification method, where the ABC classification divides based on classes. There are 3 classes, namely class A, class B, and class C.The purpose of ABC classification is to help companies to see priority inventory in storage in the sense that much is needed by consumers. The writing of this Final Project report shows that the warehouse capacity is 254.592 kg and the capacity of goods for safety stock required is 192.091 kg so that the warehouse can store goods for safety stock maintenance for the next 3 days with the remaining warehouse capacity of 62.501 kg.